2023
DOI: 10.3390/jcm12093050
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Atrial Fibrillation Treatment Strategies on Cognitive Function

Abstract: There is increasing evidence to suggest that atrial fibrillation is associated with a heightened risk of dementia. The mechanism of interaction is unclear. Atrial fibrillation-induced cerebral infarcts, hypoperfusion, systemic inflammation, and anticoagulant therapy-induced cerebral microbleeds, have been proposed to explain the link between these conditions. An understanding of the pathogenesis of atrial fibrillation-associated cognitive decline may enable the development of treatment strategies targeted towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 116 publications
0
2
0
Order By: Relevance
“…AF catheter ablation represents the cornerstone of the rhythm control strategy [3]. Theoretically, maintaining sinus rhythm could improve cerebral perfusion and could reduce cognitive decline prevalence in the long term [87,88]. In selected patients, such as some CAA patients, after an effective ablation procedure, we can, at least temporarily, suspend anticoagulant therapy, therefore reducing the bleeding risk.…”
Section: Catheter Ablation Of Atrial Fibrillationmentioning
confidence: 99%
“…AF catheter ablation represents the cornerstone of the rhythm control strategy [3]. Theoretically, maintaining sinus rhythm could improve cerebral perfusion and could reduce cognitive decline prevalence in the long term [87,88]. In selected patients, such as some CAA patients, after an effective ablation procedure, we can, at least temporarily, suspend anticoagulant therapy, therefore reducing the bleeding risk.…”
Section: Catheter Ablation Of Atrial Fibrillationmentioning
confidence: 99%
“…A meta-analysis of nine studies found that direct oral anticoagulation may reduce the risk of dementia in Afib more so than Warfarin, though the authors urge caution against overinterpretation of their findings [94]. Key questions on the effects of Afib on post-stroke brain health persist, including the cognitive impact of different modalities of rhythm control or atrial appendage occlusion and how the burden of Afib (proportion of time someone is in Afib) affects cognition [95,96]. Most studies on the impact of Afib on cognition are among individuals without stroke; more studies are needed to specifically define the role of Afib in post-stroke physical and cognitive functioning and whether various treatment options have differential impacts on post-stroke functional status and brain health.…”
Section: Atrial Fibrillationmentioning
confidence: 99%
“…In addition, modi able risk factors such as obesity, diabetes, high blood pressure and so on has been con rmed to be involved in the development of AF [5][6][7] . With AF continuous development, stroke, heart failure, myocardial infarction, even death would be happen [7][8][9][10] . So there are calling for ideal pharmacologic approaches to treat AF 11 .…”
Section: Introductionmentioning
confidence: 99%